Assessment of Farmers’ Knowledge, Practices, and Effectiveness of Control Strategies Against Storage Pests and Soil Borne Diseases in Cereal and Legume Crops in Lupane District, Zimbabwe - Zhou, Mandhlenkosi; Mlambo, Alec; Tibugari, Handsen (Journal of Tropical Plant Protection, 2026)
Smallholder farmers in semi-arid sub-Saharan Africa depend largely on both formal and informal seed systems, although the contribution of various seed types towards land cultivation remains unclear. The objectives of the study were to evaluate farmer knowledge of storage pests and soil-borne diseases, seed sourcing systems, and perceived efficiency of traditional seed storage practices for cereals and legumes in Lupane District, Zimbabwe. A questionnaire survey was administered to 400 farmers across ten wards between October 2022, and March 2023 and October 2023. A multistage sampling method was adopted in ward and farmer selection. Findings indicated that despite the fact that 97.8% of respondents used seed through government input schemes and 98.8% used commercial seed at least once, the quantities were generally low for planting. As a result, most land cultivated was planted with farm-saved seed. In relation to area planted, farm-saved seed that is traditionally treated comprised 45% of land cultivated, untreated farm-saved seed comprised 42%, while commercial seed comprised only 13%. Economic factors were the key factor in the choice of farm-saved seed. Storage crop pests (maize, rice, and cowpea weevils), were well known, while there was limited knowledge on soil-borne fungal diseases. Holes and frass were identified as damage symptoms in all crops. Combretum imberbe ashes was identified as the most used and preferred traditional seed preservation treatment. Farm-saved seeds were predominant used despite the persistent use of commercial seeds, and there is need for scientific studies of common botanicals used in seed production in semi-arid farming communities.